Clinical portrait of a patient with acute coronary syndrome and type 2 diabetes mellitus: a novel strategy for the diagnosis, prognosis and treatment - M.I. Shved; I.O. Yastremska; L.V. Levytska; V.Yu. Kuchmiy; O.A. Prokopovych; Ya.M. Kitsak; R.M. Liakhovych (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Patients with type 2 diabetes mellitus (T2DM) have a two-fold risk of coronary artery disease (CAD), and their myocardial infarction-associated mortality is 2–4 times higher compared to patients with intact carbohydrate metabolism. The purpose of the study: to determine the impact of type 2 diabetes on the severity of clinical course, changes in laboratory and instrumental findings, the prognosis and treatment strategy selection in patients with acute coronary syndrome (ACS). Materials and methods. We have examined 75 patients with ACS, which has developed on the background of T2DM (the main group), and 28 patients with ACS without T2DM (the control group). ACS with T2DM was substantially more frequent (84 % of cases) in young to middle-aged males (up to 60 years of age) who predominated compared to female patients in a 4.8 : 1 ratio. It was typical for these patients to have frequent comorbid conditions, namely: hypertension (94.7 %), metabolic syndrome (85.3 %), chronic kidney disease (30.7 %), chronic obstructive pulmonary disease (29.3 %), thyroid dysfunction (22.7 %), and such CAD risk factors (and their combinations in 89.3 % of cases) as atherogenic dyslipidemia (96.0 %), tobacco smoking (34.7 %), excessive alcohol use (32.0 %), family history of CAD and T2DM (29.3 and 61.3 % of patients, respectively). Results. The characteristic clinical feature in a patient with ACS and T2DM is a severe condition, which is due to a combined multi-vascular involvement of coronary arteries (which is 10.5 times more frequent in these patients) and larger volumes of myocardial necrosis. Such individuals have more pronounced manifestations of necrosis-resorption syndrome, a significant increase in left ventricular myocardial mass and volume due to an increase in diastolic and systolic dimensions, which suggests hypertrophy and cardiac remodeling with impaired systolic function (ejection fraction of less than 50 %) and impaired diastolic function; the latter is considered an impairment of relaxation processes. Conclusions. The clinical portrait of patients with ACS developed on the background of type 2 diabetes is characterized by the following features: men under 60 years of age with comorbid conditions and multiple risk factors for coronary artery disease, multivessel and hemodynamically severe coronary lesions (more than 33 points on the SYNTAX scale), large volume of myocardial necrosis, which determines the atypicality and severity of the disease, high grade of heart failure, a significantly higher incidence of life-threatening complications, and a high risk (over 160 points on GRACE score) of cardiac death.